Pengaruh Independensi Auditor, Strategi, Dan Kualifikasi Auditor Terhadap Kualitas Audit Di Era Society 5.0 Pada Auditor KAP Kepulauan Riau - Aulia Dewi Gizta; Novica Indriaty; Muhammad Mu’azamsyah; Chika Putri Andina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
The purpose of this study was to determine the effect of Independence, Strategy and Audit Qualifications on Audit Quality. The population of this study were all auditors who worked or served in the Riau Islands Province Public Accounting Firm, totaling 47 auditors. The sample technique used in this research is saturated technique. The method used in this research is quantitative method. Data collection is done by collecting questionnaires. Where respondents fill out a statement questionnaire related to the variable being measured. The tool used in conducting data quality tests, namely classical assumption tests, multiple linear regression and hypothesis testing is JASP (Jeffreys's Amazing Statistics Program) version 0.19.1.0. The results of this study indicate that independence has an effect on audit quality with a t value of 5.453> t table 2,015 and a significance value (Sig) of 0.001 <0.05. Then for the strategy to affect audit quality with a t value of 2.790 >t table of 2,015 and a significance value (Sig) of 0.008< 0.05. Then for the Audit Qualification variable has no effect on audit quality with the results of the calculation of the t value of 0.412 < t table of 2.015 with a significance value (Sig) of 0.682 > 0.05. With the results of calculations using these test tools, it can be concluded that the independence and audit strategy variables affect audit quality, but the qualification variable has no effect on audit quality. Keywords : Independence, Audit Strategy and Qualifications